Severe Hyperthyroidism Presenting with Acute ST Segment Elevation Myocardial Infarction - Dayan Zhou; Zongjie Qu; Hao Wang; Zhe Wang; Qiang Xu (Case Reports in Cardiology, 2015)
Introduction. Acute myocardial infarction is life-threatening. A cardiac troponin rise accompanied by typical symptoms, ST elevation or depression is diagnostic of acute myocardial infarction. Here, we report an unusual case of a female who was admitted with chest pain. However, she did not present with a typical profile of an acute myocardial infarction patient. Case Presentation. A 66-year-old Han nationality female presented with chest pain. The electrocardiogram (ECG) revealed arched ST segment elevations and troponin was elevated. However, the coronary angiography showed a normal coronary arterial system. Thyroid function tests showed that this patient had severe hyperthyroidism. Conclusion. Our case highlights the possibility that hyperthyroidism may cause a large area of myocardium injury and ECG ST segment elevation. We suggest routine thyroid function testing in patients with chest pain.